Effectiveness of Nissen fundoplication versus anterior and posterior partial fundoplications for treatment of gastro-esophageal reflux disease: a systematic review protocol. (May 2018) - Marshall-Webb, Matthew; Peters, Micah D.J.; Bright, Tim; Watson, David I.
Abstract : Review question/objective: The objective of this review is to determine the relative effectiveness of Nissen fundoplication compared to anterior and posterior partial fundoplication in controlling the symptoms of gastro-esophageal reflux disease and reducing their side effect profile in adults. The specific questions posed by this review are: what is the effectiveness of Nissen fundoplication in comparison to anterior partial fundoplication (90 degree, 120 degree and 180 degree) and posterior 270 degree fundoplication in terms of symptom control of gastro-esophageal reflux disease, and what are the side effects of these surgical interventions?